A Review on Evolution of Cryptocurrencies using Blockchain - Hema, K; Prasad, A. Ravi; Kumar, J. Kishore (International Journal of Computer Sciences and Engineering, 2025)
Cryptocurrency, which operates as a Peer to Peer Electronic Cash System. Cryptocurrency has a potential to be a major means of payment for e-commerce. In Cryptocurrency the word -"Crypto" refers to various encryption algorithms and cryptographic techniques are employed. Cryptocurrency has numerous latent value propositions and long-term use cases including Distributed Ledger Technology (DLT) and Blockchain innovations. This technology is not issued by any central authority and it is theoretically not effecting to any Government interference. The first Cryptocurrency based on Blockchain was Bitcoin, which is still the most popular and valuable. The success of Bitcoin brought number of competing Cryptocurrencies like -Altcoins. For example Altcoins are- Litecoin, Namecoin, Ethereum, Peercoin, Dogecoin, Monero, EOS, and Cardano etc., At present there are literally thousands of Cryptocurrencies in existence, with an aggregate market value around $200 billion. But the future of Cryptocurrency is impossible to predict, and although it is unlikely that Cryptocurrency will eliminate trusted intermediaries like Financial Payments, Settlements, Clearing, Supply Chain, Agriculture, Voting, Data Protection Mechanisms, Crowd-funding, Decentralized business applications and Services. There may be benefits of Cryptocurrencies towards hype-financed research and development in DLT and Blockchain infrastructure. The main purpose of this study is to narrate the evolution of Cryptocurrency using Blockchain Technology. The study also includes the growth of technology and the challenges that are faced at the time of development. However there are inherent difficulties in regulating the cryptocurrency market, which will be discussed in detail in this paper.